Long-Term Results of Medical and Surgical Methods for Elimination of the Internal Anal Sphincter Spasm in Chronic Anal Fissure (NCT03855046) - S. I. Achkasov; R. Yu. Khryukin; E. E. Zharkov; A. A. Ponomarenko; O. Yu. Fomenko; N. I. Klopkov; Z. Z. Kamaeva; E. Yu. Lebedeva; K. I. Sagidova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: evaluation of long-term results of injection of botulinum toxin type A into the internal anal sphincter and performing lateral internal sphincterotomy in combination with excision of chronic anal fissure.Materials and methods. The study included 176 patients (73 (41.5 %) men and 103 (58.5 %) women) older than 18 years; randomization into the compared groups was carried out by random number generation in a computer program. Patients, researchers and surgeons were not blinded. Patients of the main group underwent fissure excision in combination with relaxation of the internal anal sphincter by botulinum toxin type A (BTA) at a dosage of 40 units, patients of the control group underwent lateral internal sphincterotomy (LIS) with excision of chronic anal fissure. Long-term results of complex treatment were studied in 126 patients (54 (43 %) men and 72 (57 %) women), the median follow-up was 12.3 (12.2; 15.7) months. Statistical analysis was carried out in the program Statistica 13.3 (TIBCO Software Inc., USA).Results. In the long-term postoperative period, the indicators of mean resting anal pressure were lower in the LIS group (p = 0.04). The compared groups were comparable in terms of the level mean squeeze anal pressure (p = 0.69); however, in patients of the BTA group, the level of this indicator increased over time (p = 0.001). None of the patients of the compared groups had anal incontinence and relapse of the disease.Discussion. In the framework of the performed study, in some patients from the compared groups, spasm of the internal anal sphincter persisted throughout the observation period, and in some patients it occurred again, while no signs of relapse fissure were detected. The functional and clinical results of treatment obtained by us cast doubt on the exclusivity of the increased tone of the internal anal sphincter as the main link in the pathogenesis of chronic anal fissure in some patients and indicates the presence of other factors in combination with which the course of the disease is determined. The above facts do not exclude the possibility of recurrence of anal fissure in a more distant period of observation.Conclusion. Medical relaxation with botulinum toxin type A at a dosage of 40 units can serve as an alternative to lateral internal sphincterotomy as a method of eliminating spasm of the internal anal sphincter